ADVANCE CARE PLANNING IN RESIDENTIAL CARE: 5 YEARS OF CONTINUOUS QUALITY IMPROVEMENT. Issue 2 (1st June 2013) - Nicholes, M; Billings, S; Perta, A; Melican, G
Abstract : Aim: Until recently Australia has lacked guidelines and practical examples from the field on best practice for implementing Advance Care Planning (ACP) in Residential Care Facilities (RCFs). In 2008 the Victorian Department of Health funded an ACP programme at Alfred Health. This presentation will detail our experience of 5 years of continuous quality improvement in ACP in RCFs. Methods: Alfred Health has three RCFs on site at Caulfield Hospital, which provides care to 120 permanent residents. Over the 5 year time period, initiatives were implemented in an effort to improve ACP processes and outcomes. These included: dedicated ACP staffing time in partnering with staff in RCFs, education and training of staff, development of documents, implementation of systems and procedures, engagement of GP's and the development of an auditing tool to measure change. Results: Prior to the implementation of ACP in 2008, there were no obvious systems in place to support ACP. Documentation of resident end of life care wishes and NFR status were unclear and confusing for staff to follow. The 2012 audit of RCFs at Caulfield Hospital reveal that 89% of residents participated in ACP and 48% of residents have clear medical treatment plans which have been completed by the GP. Conclusion: Our experience provides a successful example of how to implement quality improvement in ACP in RCFs over a realistic time frame with limited resources.